Karakteristik dan Persoalan Ekonomi Masyarakat Petani dan Nelayan pada Kawasan Pantai di Torosiaje Kabupaten Pohuwatu - Erlyna Wida Riptanti (Caraka Tani: Journal of Sustainable Agriculture, 2005)
High poverty level because of coastal area community characteristic include low of social-economic living,minimum access to environment resources, and economic problems. Such as Torosiaje coastal area community in Pohuwato regency, where used as research area of wallacea expedition 2005. For this need investigate characteristic and economic problem that have coastal area community. From investigate knew education level average area low, so influence to business management both agriculture and fishing are not good. Beside low of human resources, economic problem include harvest fail, low of working capital, low of agriculture product price and less of attention from government. It need cooperation among farmers, fisher, government and other stakeholder to increase prosperous of the coastal area community.